Investigation of water retention and mechanical properties of bacterial cellulose for wound care applications - Sundaravadanam Vishnu Vadanan (2015)
Bacterial cellulose (BC) produced by the bacteria Gluconacetobacter xylinum is of high purity and crystallinity and has high water content due to the ultrafine highly fibrous structure which is similar to that of collagen[1]. The highly fibrous network contributes to increased mechanical strength. Due to these desirable properties, it finds its uses in electronics, paper products and biomedical devices. Water holding capacity of cellulose is an important factor for BC application as wound dressing. It is necessary to understand the right amount of water retained by BC, as this will have implications on the retention of other molecules such as antimicrobial agents. Presence of moisture assists in easy and painless wound healing and formation of new tissue. The mechanical character of BC should also be taken into consideration as it is essential for a biomaterial to be strong and stiff. The main objective of this study is to compare the different carbon sources cellulose yield under static conditions. Two batches of cellulose samples were incubated for different number of days and were analyzed. Structural morphology of the cellulose samples was observed using scanning electron microscopy imaging technique. BC produced from different carbon sources consists of microfibrils which were several nanometers long and about 40-80nm thick. Water retention capacity of the different samples was studied when subjected to different experimental conditions such as temperature and water soaking time. Mechanical characterization of the samples was investigated by measuring stress, strain and Young’s modulus.